A novel social-network-analysis-based approach for analyzing complex network of actors involved in accessibility of anti-cancer medications in Iran - Kamran Bagheri Lankarani; Leila Zarei; Esmaeil Alinezhad; Adel Sadeghdoost (Health Research Policy and Systems)
Abstract Background The access to anti-cancer medications is influenced by policies formed via the convergence of various stakeholders. The aim of this study is to identify and analyse the stakeholders involved in formulating and implementing policies related to the accessibility of anti-cancer medications in Iran and their interactions that are relevant to the outcomes of these policies for the first time. Methods To achieve the objectives, a novel multistage social network analysis (SNA)-based approach that includes three phases is proposed. First, the actors were identified by a team consisting of multidisciplinary knowledgeable experts through 15 comprehensive interviews. Then, the influence relationships of these actors were comprehensively analysed through in-depth interviews with nine key informants involved in pharmaceutical policies through a structured questionnaire. Finally, a novel network of actors was determined accordingly, and a SNA-based approach proposed to reveal the intrinsic roles and various aspects of the importance of the network’s actors. Results The study identified a total of 45 actors, which were then classified into 4 categories on the basis of their public or private nature and their foreign or domestic origin. This established network helped in creating a comprehensive view of the main actors, and can help policymakers to solve the problems related to access to anti-cancer medications more effectively and prevent the creation of these problems in the future. In this way, the network identified specific actors that can benefit from increased attention and dialogue. The computational results revealed that the Iran Food and Drug Administration (IFDA), Pharmaceutical Importer Companies (PharIc) and Pharmaceutical Manufacturing Companies (PharMC) were highly important actors in terms of their connectivity to other actors. Additionally, law enforcement agencies (LEA) have shown limited effectiveness within this network. Conclusions This study highlights the importance of complex relationships among various actors and proposes a novel SNA-based approach to analyse them. Regarding the main steps of the proposed approach and the findings, it is imperative for pharmaceutical policy plans to involve a diverse group of experts from the beginning, prioritizing the preferences of stakeholders, and providing a patient-centred approach to prevent the worsening of resource shortages.